ANALISIS PENDAPATAN DAN PEMASARAN USAHATANI BROKOLI (Brassica oleracea L.) DI DESA MUARA PERIKAN KECAMATAN PAGARALAM SELATAN KOTAMADYA PAGARALAM - Wijaya, Denny; Utama, Satria Putra; Cahyadinata, Indra (Jurnal AGRISEP, 2012)
This research was conducted with the purpose to : (1) calculate farm income of broccoli, (2) investigate marketing channels of broccoli and (3) calculate its marketing margin. Research area is determined purposively, i.e., Muara Perikan Village Subdistrict South Pagaralam. Respondents of broccoli farmers are censused involving 14 farmers while marketing institutions are determined with Snowball Sampling. The research showed that averaged farm income is equal to Rp.11.026.213/farming, or Rp.34.852.536/Ha and efficiency of farm broccoli is equal to 3,56. This means that broccoli farming in research area is efficient. In terms of marketing channel, three marketing channels were found. In this study, only two channels were studied. In the first marketing channels, farmers share was high at 66.67% of the final sale price merchants. Total margin from one marketing channel activity of Rp. 3000, the total profit margin of Rp. 2295.26. In the second channels, the percentage share of farmers was 51.43%, with marketing margin of Rp. 5666.67 and the total profit of Rp. 4673.07